1997
DOI: 10.1016/s0006-3495(97)78330-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-transmission electron microscopy of a superstructure of fluid dioleoylphosphatidylcholine (DOPC) membranes

Abstract: Using cryo-transmission electron microscopy, we have obtained abundant and reproducible evidence for a superstructure of dioleoylphosphatidylcholine (DOPC) bilayers. Dispersions of vesicles were prepared by gentle shaking of a 2% suspension of DOPC in water followed in part by extrusion through a porous technical membrane. Sampling and cryofixation took place at various times within 3 weeks after the preparation. From the micrographs we infer that the small fraction of vesicles enclosing one another develop pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Untrapped CF buffer was separated from the liposomes by gel filtration over a PD-10 desalting column from Amersham Biosciences (Uppsala, Sweden). It has been shown that bilayers formed from DOPC and DOPC/cholesterol under certain conditions have a tendency to transform into inverted structures (23,24). However, as judged from cryotransmission electron microscopy (cryo-TEM), the freshly prepared liposome samples used in these experiments did not contain any such structures.…”
Section: Liposome Preparationmentioning
confidence: 86%
“…Untrapped CF buffer was separated from the liposomes by gel filtration over a PD-10 desalting column from Amersham Biosciences (Uppsala, Sweden). It has been shown that bilayers formed from DOPC and DOPC/cholesterol under certain conditions have a tendency to transform into inverted structures (23,24). However, as judged from cryotransmission electron microscopy (cryo-TEM), the freshly prepared liposome samples used in these experiments did not contain any such structures.…”
Section: Liposome Preparationmentioning
confidence: 86%
“…Therefore, it is not possible, without knowing the nature of the saddle-like actors, to compare the experimentally observed lattice spacings with the calculated ones. This suggests however, because experiments on different systems have reported lattice spacing ranging from 4 nm (Klösgen and Helfrich, 1997) to 75 nm (Meyer et al, 1990), that the possible saddle-like defects involved might have different origins.…”
Section: Possible Relationship With the Experimentally Observed Egg-cartons Superstructures Of Membranesmentioning
confidence: 99%
“…Another reason for postulating the existence of such superstructures is some evidence of anomalous membrane roughness suggested by studies of membrane adhesion (Servuss and Helfrich, 1989). Recent experiments using cryo-transmission electron microscopy on dilute vesicle dispersions have also shown the formation of disordered superstructures in fluid dioleoyl-phosphatidylcholine membranes (Klösgen and Helfrich, 1997).…”
Section: Possible Relationship With the Experimentally Observed Egg-cartons Superstructures Of Membranesmentioning
confidence: 99%
“…The associated decrease of the surface area of the vesicle was interpreted in both cases as a loss of lipids from the vesicle membrane. Sandre, using fluorescence microscopy, observed some small fluorescent particles close to de-swelling vesicles that he interpreted in terms of a concentrated lipid superstructure (bicontinuous cubic phase; Kummrow and Helfrich, 1996;Klösgen and Helfrich, 1997), formed by the collapse of the excess of membrane. These lipid wells might be involved in the behavior observed in this work, the transition being possibly associated with the strong applied osmotic pressure, since neither significant budding nor daughter vesicles were observed using phase contrast microscopy.…”
Section: Osmotic Pressurementioning
confidence: 99%